2004
DOI: 10.1038/sj.bjc.6602041
|View full text |Cite|
|
Sign up to set email alerts
|

Characterisation of human kallikrein 6/protease M expression in ovarian cancer

Abstract: Kallikrein 6 (hK6, also known as protease M/zyme/neurosin) is a member of the human kallikrein gene family. We have previously cloned the cDNA for this gene by differential display and shown the overexpression of the mRNA in breast and ovarian primary tumour tissues and cell lines. To thoroughly characterise the expression of this kallikrein in ovarian cancer, we have developed a novel monoclonal antibody specific to hK6 and employed it in immunohistochemistry with a wide range of ovarian tumour samples. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
3
34
0
4
Order By: Relevance
“…High KLK6 mRNA expression was associated with the presence of serous ovarian cancer and late stage disease. These results are similar to previous studies, which found increased KLK6 expression in ovarian cancers when compared to normal ovarian tissue (Anisowicz et al, 1996;Tanimoto et al, 2001;Ni et al, 2004). Interestingly, previous studies have also associated high KLK6 serum levels with advanced ovarian cancer (stage III/IV) and serous tumour histology (Hoffman et al, 2002;Shan et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…High KLK6 mRNA expression was associated with the presence of serous ovarian cancer and late stage disease. These results are similar to previous studies, which found increased KLK6 expression in ovarian cancers when compared to normal ovarian tissue (Anisowicz et al, 1996;Tanimoto et al, 2001;Ni et al, 2004). Interestingly, previous studies have also associated high KLK6 serum levels with advanced ovarian cancer (stage III/IV) and serous tumour histology (Hoffman et al, 2002;Shan et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Lastly, chromosome 19q13 is reportedly rearranged in numerous types of solid tumours (Whang-Peng et al, 1984;Tanaka et al, 1989;Bello and Rey, 1990;Pejovic et al, 1991Pejovic et al, , 1992Jenkins et al, 1993). Potential gene amplification of KLK6 in ovarian cancer has also been suggested (Ni et al, 2004). Therefore, the role of chromosomal rearrangements of the KLK locus in cancer should be examined in future investigations.…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of KLK protein dysregulation in ovarian cancer was compiled from the results of 17 studies (Dong et al, 2001;Luo et al, 2001Luo et al, , 2003Tanimoto et al, 2001;Hoffman et al, 2002;Yousef et al, , 2003bBorgono et al, 2003;Diamandis et al, 2003;Ni et al, 2004;Scorilas et al, 2004;Xi et al, 2004;Prezas et al, 2006;Shan et al, 2007;Bayani et al, 2008;Shaw and Diamandis, 2008). Chromosomal aberration in ovarian cancer was extracted from the Progenetix comparative genomic hybridisation database available as of January 2009 (Baudis and Cleary, 2001).…”
Section: Bioinformatic Analysismentioning
confidence: 99%